2015
DOI: 10.5455/ijmsph.2015.25062015315
|View full text |Cite
|
Sign up to set email alerts
|

A study of knowledge, attitude, and practices regarding biomedical waste management among the health-care workers in a multispeciality teaching hospital at Delhi

Abstract: Biomedical Wastes are defined as wastes that are generated during the diagnosis, treatment or immunization of human beings or animals, or in research activities pertaining thereto, or in the production or testing of biological [1]. Studies have shown that 85% of the waste generated in health care establishments is non-hazardous, about 10% is infectious Background: There is an increased global awareness among health professionals about the health hazards owing to biomedical waste (BMW) and appropriate managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
(4 reference statements)
3
10
1
Order By: Relevance
“…This was similar to the results from the study conducted by Sehgal et al, where correct color coding for waste disposal was known to 80% of sanitary staff. 8 However in the present study, 45.7% did not know about biohazard symbols and only 54.3% were aware of the diseases that are spread by improper waste management. In the study conducted by Mathur et al in Allahabad, knowledge regarding the potential of transmission of diseases through biomedical waste was found among only 27% sanitary staff.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…This was similar to the results from the study conducted by Sehgal et al, where correct color coding for waste disposal was known to 80% of sanitary staff. 8 However in the present study, 45.7% did not know about biohazard symbols and only 54.3% were aware of the diseases that are spread by improper waste management. In the study conducted by Mathur et al in Allahabad, knowledge regarding the potential of transmission of diseases through biomedical waste was found among only 27% sanitary staff.…”
Section: Discussioncontrasting
confidence: 70%
“…Sehgal RK et al, reported that the use of protective clothing to prevent infections was found to be 100% among all the categories of health care workers whereas a study conducted by Chudasama et al, in Rajkot reported that use of personal protective measures while handling biomedical waste was 74.1% among sanitary workers. 8,9 In the present study, 51.9% of workers had received vaccine against Hepatitis B infection while 54.3% were immunized against tetanus. Kumar et al, from a study in Nainital reported that 75% of the sanitary staff were not vaccinated against Hepatitis B.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…These findings are in contrast to the findings of a study conducted by Sehgal et al in which 95% participants were of the view that safe management of health-care waste is not the sole responsibility of the Government, 92.5% agreed that safe management of health-care waste is not an extra burden on them / institution and 81.7% were of the view that BMW management does not increase financial burden on hospital management. 12 In our study, majority (83.2%) of the participants agreed that segregation of BMW using colour coding is a must, and the percentage improved significantly after training. According to a study of Manchanda et al, 90% participants agreed that use of colour code for segregation is a must.…”
mentioning
confidence: 49%